2015
DOI: 10.1111/padm.12144
|View full text |Cite
|
Sign up to set email alerts
|

Managing Institutional Complexity in Public Sector Reform: Hybridization in Front‐line Service Organizations

Abstract: In this article, we explore how public front‐line service organizations respond to contradictory demands for institutional reform and the types of hybridization this entails. Our research context is a major administrative welfare reform in Norway characterized by a dominant New Public Management (NPM) logic of uniform user service and central administrative control, and a subordinate post‐NPM logic of holistic user service and local organizational autonomy. We elucidate four types of responses by the front‐lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
120
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 54 publications
(148 reference statements)
0
120
1
2
Order By: Relevance
“…These articles include those on: Norwegian labour and welfare reform (Fossestol et al. ); higher education reforms in Sweden, the UK, and the Netherlands (Teelken ); and reforms in Scotland and Ireland (McDermott et al. ).…”
Section: An Outline Of the Articlesmentioning
confidence: 99%
“…These articles include those on: Norwegian labour and welfare reform (Fossestol et al. ); higher education reforms in Sweden, the UK, and the Netherlands (Teelken ); and reforms in Scotland and Ireland (McDermott et al. ).…”
Section: An Outline Of the Articlesmentioning
confidence: 99%
“…While for some scholars the co-existence of logics and the necessity to deal with different institutionalized demands -even if through compartmentalization -is sufficient to constitute hybridity (e.g., Fossestøl et al, 2015;Skelcher & Smith, 2015;Pache & Santos, 2013a), for others a certain mixing of elements is required (e.g., Battilana & Lee, 2014). Yet another group of scholars see complexity as a "precondition for hybridity, meaning that hybridity always implies some form of complexity" (Christensen, 2014, p. 163; see also Brandsen & Karré, 2011).…”
Section: Conceptual Background: Different Forms Of Hybriditymentioning
confidence: 99%
“…Waldorff, Reay, & Goodrick, 2013), in labor and welfare administration (e.g., Fossestøl, Breit, Andreassen, & Klemsdal, 2015), or in the identities of public-sector employees (e.g., Meyer & Hammerschmid, 2006). While the focus of attention has mostly been on organizational design and specific organizational phenomena, it has rarely been extended to the institutional framework -that is, to the question of how hybridity may affect the very architecture of the state and of public administration more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…This article focuses on structural hybridity; while identity and role hybridity are also studied elsewhere, for example within the welfare and health sector (cf. Denis et al ; Fossestøl et al ; McDermott et al ). The growing literature on collaborative public management has tended to treat networks as distinct from hierarchies, but recent research has shown that when actors organize to reach policy goals in practice, traces from both organizing principles are present (McGuire ; McDermott et al ).…”
Section: Designing Collaborative Disaster Management: Hierarchy Netwmentioning
confidence: 99%